All the Feels / Tous les sens Affect and Writing in Canada / Affect et écriture au Canada - Carrière, Marie; Mathis-Moser, Ursula; Dobson, Kit (University of Alberta Press, 2021)
All the Feels / Tous les sens presents research into emotion and cognition in Canadian, Indigenous, and Québécois writings in English or French. Affect is both internal and external, private and public; with its fluid boundaries, it represents a productive dimension for literary analysis. The emerging field of affect studies makes vital claims about ethical impulses, social justice, and critical resistance, and thus much is at stake when we adopt affective reading practices. The contributors ask what we can learn from reading contemporary literatures through this lens. Unique and timely, readable and teachable, this collection is a welcome resource for scholars of literature, feminism, philosophy, and transnational studies as well as anyone who yearns to imagine the world differently. Contributors: Nicole Brossard, Marie Carrière, Matthew Cormier, Kit Dobson, Nicoletta Dolce, Louise Dupré, Margery Fee, Ana María Fraile-Marcos, Smaro Kamboureli, Aaron Kreuter, Daniel Laforest, Carmen Mata Barreiro, Ursula Mathis-Moser, Heather Milne, Eric Schmaltz, Maïté Snauwaert, Jeanette den Toonder